Menuai Hunian: Strategi Komunikasi Tapera oleh PT CJ Logistics Service Indonesia - Setiagiri, Agung; Wijanarko, Totok Ony; Pratama, Andi Agustian; Hutapea, Edison Bonartu (FISIP Universitas Bung Karno, 2025)
This article discusses Corporate Communication Strategy in the People's Housing Savings Program (Descriptive Study at PT. CJ Logistics Service Indonesia). This research is motivated by the government's plan to implement a people's housing savings program (TAPERA) to all workers, especially private employees working in the Logistics and Transportation sectors. The purpose of this study is to provide a clear direction in the company's policy communication strategy related to the TAPERA policy communication strategy at PT. CJ Logistics Service Indonesia. This study uses a descriptive qualitative research method and in collecting, managing and analyzing data. The results of the author's research explain that the communication strategy implemented by PT. CJ Logistics Service Indonesia in the People's Housing Savings (TAPERA) program has a very important role in facilitating employee understanding and acceptance of this policy. The implementation of an effective communication strategy will greatly determine how well the TAPERA policy is accepted and understood by employees, and the extent to which this policy can have a positive impact on employee social welfare. Keywords: Corporate communication strategy, people's housing savings (TAPERA), descriptive qualitative, organizational control, public policy.